The legal conceptualization of sex trafficking in Argentina. Political languages and criminal definitions - Coppa, Lucía Inés (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
The aim of this article is to recapitulate some analytical keys around the notion of trafficking as a diffuse criminal concept as well as its implications for criminal processes. In the first place, I review some theoretical coordinates to think about law as a discourse of truth. In the second place, I locate debates about the definition of trafficking as a crime within feminist disputes around the understanding of sexual commerce. By last, I reflect on links between referred theorizing and its specific translation in criminal field.
Keywords: Trafficking; sexual commerce; legal discourse; justice; criminal process